Developing Programming Competence Among Physics Education Students With Multi-Platform E-Learning During COVID-19 - Syahid, Muhammad Taufik; Sutrio, Sutrio; Wahyudi, Wahyudi; Zuhdi, Muhammad; Arduha, Jannatin (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2023)
This research examines the effectiveness of a multi-platform e-learning approach in developing programming competence among physics education students at Mataram University's Faculty of Teaching and Education during the COVID-19 pandemic. The R2D2 model, an iterative and cyclical constructivist learning design process emphasizing creative learning experiences, serves as the methodological framework. Data collection employs questionnaires and tests. The research yields two primary findings: the development of a multi-platform e-learning media for a computer programming course by combining features from SIA, SPADA Unram, YouTube Channel, Google Drive, and WhatsApp groups; and student learning outcomes falling within the "satisfaction" category. Statistical analysis of class A and B data (means and standard deviations: 76.429/0.782 and 74.57/1.06, respectively) reveals insufficient evidence to conclude a significant difference in data variability between the two groups. Keywords: Programming Competence, Multi-platform e-Learning, Physics Education Students, Covid-19.